Parotid gland tumors: comparison of conventional and diffusion-weighted MRI findings with histopathological results - Karaman, Can Zafer (Dentomaxillofac Radiol, 2021)
OBJECTIVES: The aim of this study was to investigate the relationship between pathological classification of parotid gland tumors and conventional MRI – diffusion-weighted imaging findings and also contribute the possible effect of apparent diffusion coefficient (ADC) to diagnosis. METHODS: 60 patients with parotid masses diagnosed using histopathology and/or cytology were enrolled in this retrospective study. All patients were evaluated using a 1.5 T MRI. Demographic features, conventional MRI findings, and ADC values (mean, minimum, maximum, and relative) were recorded. MRI findings and ADC values were compared between benign–malignant groups and pleomorphic adenoma vs Warthin’s tumor groups. RESULTS: 60 tumors (48 benign, 12 malignant) were evaluated in a total of 60 patients (39 males, 21 females). The mean age was 59 (±14, 18–86) years old; the mean lesion size was 26 (±10, 11–61) mm. On the texture of conventional MRI, T2 dominantly hyperintense/with hypointensity signal was seen in 87% of pleomorphic adenomas and T2 dominantly hypointense/with hyperintesity signal was encountered in 64% of all Warthin’s tumors. Seven (28%) Warthin’s tumors were misdiagnosed as pleomorphic adenomas and two others (8%) as malignant tumors. The commonly used mean ADC value was 1.6 ± 0.6 × 10(–3) mm(2) s(−1) for benign tumors, 0.8 ± 0.3 × 10(–3) mm(2) s(−1) for malign tumors, 1 (0.9–1.8) × 10(–3) mm(2) s(−1) for Warthin’s tumors, and 1.9 ± 0.3 × 10(–3) mm(2) s(−1) for pleomorphic adenomas. There was a statistically significant difference in ADC values between benign-malignant tumors and pleomorphic adenomas-Warthin’s tumors. CONCLUSIONS: Warthin’s tumor may occasionally be misdiagnosed as pleomorphic adenoma and malignant tumor because of variable morphologic features. In addition to benign–malignant differentiation, the added ADC measurement may also be useful for differentiating Warthin’s tumors from pleomorphic adenomas.